Antiproliferative activity of antimicrobial peptides and bioactive compounds from the mangrove Glutamicibacter mysorens - Karthik, Yalpi; Ishwara Kalyani, Manjula; Krishnappa, Srinivasa; Devappa, Ramakrishna; Anjali Goud, Chengeshpur; Ramakrishna, Krishnaveni; Wani, Muneeb Ahmad; Alkafafy, Mohamed; Hussen Abduljabbar, Maram; Alswat, Amal S.; Sayed, Samy M.; Mushtaq, Muntazir (Frontiers in Microbiology, 2023)
The Glutamicibacter group of microbes is known for antibiotic and enzyme production. Antibiotics and enzymes produced by them are important in the control, protection, and treatment of chronic human diseases. In this study, the Glutamicibacter mysorens (G. mysorens) strain MW647910.1 was isolated from mangrove soil in the Mangalore region of India. After optimization of growth conditions for G. mysorens on starch casein agar media, the micromorphology of G. mysorens was found to be spirally coiled spore chain, each spore visualized as an elongated cylindrical hairy appearance with curved edges visualized through Field Emission Scanning Electron Microscopy (FESEM) analysis. The culture phenotype with filamentous mycelia, brown pigmentation, and ash-colored spore production was observed. The intracellular extract of G. mysorens characterized through GCMS analysis detected bioactive compounds reported for pharmacological applications. The majority of bioactive compounds identified in intracellular extract when compared to the NIST library revealed molecular weight ranging below 1kgmole-1. The Sephadex G-10 could result in 10.66-fold purification and eluted peak protein fraction showed significant anticancer activity on the PC3 cell line. Liquid Chromatography–Mass Spectrometry (LC-MS) analysis revealed Kinetin-9-ribose and Embinin with a molecular weight below 1kDa. This study showed small molecular weight compounds of microbial origin possess dual roles, acting both as antimicrobial peptides (AMPs) and anticancer peptides (ACPs).